"Raíñas de pedra": a Humanizing Review of Inés de Castro’s Life and Death - Suárez Quintas, Soraya (Madrygal. Revista de Estudios Gallegos, 2015)
The tragic love between Pedro I from Portugal and Inés de Castro became, in its earlier stages, a recurrent theme of the Portuguese, Spanish and European cultural scene. The dead queen came to represent the universal myth of the innocent woman sacrificed due to the Reason of State and she became the personification of the victory of love beyond death. However, despite its strong connection with Galicia, this figure was excluded from Galician literature for many years. This article’s purpose is to review and analyse the main work that introduced the figure of Inés de Castro to the Galician literary scene, Raíñas de Pedra, by Cándido Pazó, emphasising its originality and innovation in relation to the rest of the corpus.
Keywords: Inés de Castro; Raíñas de pedra; Cándido Pazó.